Design and tuning of a cell-penetrating albumin derivative as a versatile nanovehicle for intracellular drug delivery - Ichimizu, S.; Watanabe, H.; Maeda, H.; Hamasaki, K.; Nakamura, Y.; Chuang, Victor; Kinoshita, R.; Nishida, K.; Tanaka, R.; Enoki, Y.; Ishima, Y.; Kuniyasu, A.; et al. (Elsevier, 2018)
© 2018 Human serum albumin (HSA) is a superior carrier for delivering extracellular drugs. However, the development of a cell-penetrating HSA remains a great challenge due to its low membrane permeability. We report herein on the design of a series of palmitoyl-poly-arginine peptides (CPPs) and an evaluation of their cell-penetrating effects after forming a complex with HSA for use in intracellular drug delivery. The palmitoyl CPPs forms a stable complex with HSA by anchoring itself to the high affinity palmitate binding sites of HSA. Among the CPPs evaluated, a cyclic polypeptide composed of D-dodecaarginines, palmitoyl-cyclic-(D-Arg) 12 was the most effective for facilitating the cellular uptake of HSA by HeLa cells. Such a superior cell-penetrating capability is primarily mediated by macropinocytosis. The effect of the CPP on pharmacological activity was examined using three drugs loaded in HSA via three different methods: a) an HSA-paclitaxel complex, b) an HSA-doxorubicin covalent conjugate and c) an HSA-thioredoxin fusion protein. The results showed that cell-penetrating efficiency was increased with a corresponding and significant enhancement in pharmacological activity. In conclusion, palmitoyl-cyclic-(D-Arg) 12 /HSA is a versatile cell-penetrating drug delivery system with great potential for use as a nano-carrier for a wide diversity of pharmaceutical applications.